Food Poverty and its Causes in Pakistan (The Pakistan Development Review, 1991)
The issue of malnutrition is vital in Pakistan. Recent empirical literature on this issue highlights some causes of poverty and malnutrition such as lower purchasing power of money, larger household size, low education, large number of dependents, age of the head of the household etc. [See Ehtisham and Ludlow (1989) and Havinga et al. (1989)]. But we feel that much more can be explored other than what previous literature has contributed to explain the causes of poverty and 'malnutrition in Pakistan. For example how the poor perceive hunger or starvation in society, the role of traditional diet patterns in malnourishment and critical evaluation of poverty indices. Such information is also important for the correct application of food policies in the country. 1Wo steps are needed to explore this issue: 1. Correct evaluation of the severity of poverty; and 2. To collect maximum information about the causes of poverty.